Dampak Artificial Intelegence (AI) dan Motivasi Belajar Terhadap Hasil Belajar Mahasiswa - Nuromavita, Inka; Ian , Muhammad Rezki (Fakultas Ekonomika dan Bisnis Universitas Selamat Sri, 2025)
The purpose of this study was to analyze Artificial Intelligence, and Learning Motivation on Learning Outcomes of Selamat Sri University students. This sampling method uses a random sampling technique and the number of samples in this study was 89 students. The data used is primary data. Data was obtained directly from Selamat Sri University students through a questionnaire method. Primary data was then processed and analyzed using SPSS. The collected data was then analyzed using multiple linear regression. The results of this study indicate that Artificial Intelligence has a positive and significant effect on Student Learning Outcomes, and Learning Motivation has a positive and significant effect on student learning outcomes.